Leadership with Social and Emotional Intelligence - Tamengkel, Lucky (AIBPM Publisher, 2019)
This study aims to analyze the influence of social intelligence and emotional intelligence of leaders on job satisfaction. This study uses a survey method with a quantitative descriptive approach. The location of the study was carried out at the Hospital Prof. Kandou, Manado. The population of this study were all employees at the hospital Prof. Kandou, Manado, with a sample of 150 employees in determining the sample used proportional random sampling technique. The data that has been netted with a questionnaire is then rated and tabulated for further analysis using multiple regression. The results showed that the variables of social intelligence and emotional intelligence had a positive and significant effect on job satisfaction.